Evaluation of the linus (LBI) 2.0 programme in developing basic reading skills among ESL lower primary pupils - Bokhari, Rosseliiah (2016)
In line with the launching of the Malaysia Education Development Plan (PPPM), the first English Language Literacy intervention (LBI) 2.0 programme was implemented in the Malaysian primary education curriculum in 2013. The programme which was introduced for lower primary pupils without learning disabilities, but who are unable to acquire basic literacy in English Language from the mainstream classes, emphasizes phonological awareness, phonics, vocabulary, and reading comprehension. It aims to improve the literacy outcomes for the identified learners. This study focuses on the evaluation of the LINUS (LBI) 2.0 programme. Specifically, it sought to evaluate the effectiveness of the programme in developing the lower primary school’s pupils’ reading skills and to examine teacher’s views towards the programme in terms of its content, resources and facilities, training and support as well as its implementation. Both qualitative and quantitative data were utilized in the study. The quantitative data were collected via a questionnaire and the qualitative data via semi-structured interviews and observation of the teaching and learning in the LINUS (LBI) 2.0 classroom. In total, 200 teachers from six districts in Sarawak participated in the study. Quantitative data were analysed using descriptive analysis whilst the qualitative data from the interviews and class observations were analysed based on the domains focused in the questionnaire. The findings of the study revealed that overall there was a positive feedback of the LINUS (LBI) 2.0 programme on the reading ability of the pupils involved in the programme. The results also showed that there are strengths and weaknesses in the implementation of the programme. In light of the results, this study concludes by making recommendations for the improvement of the programme, in particular with the aim of developing reading literacy of the identified pupils.